Acute effects of the 2nd generation calcium antagonists (nicardipine, nitrendipine) on cardiac and peripheral hemodynamics and left ventricular diastolic function in essential hypertension - Isik, A.; Luleci, C.; Donder, E.; Celebi, H.; Eren, O.; Arslan, N. (My University, 1992)
[Abstract Not Available]
Keywords: calcium antagonist; nicardipine; nitrendipine; adult; aged; article; blood pressure; clinical article; drug effect; drug response; essential hypertension; female; heart left ventricle function; heart output; heart rate; hemodynamics; human; male; oral drug administration; pressoreceptor